If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x = -7x + 9 + x(4x + 6) Reorder the terms: x = -7x + 9 + x(6 + 4x) x = -7x + 9 + (6 * x + 4x * x) x = -7x + 9 + (6x + 4x2) Reorder the terms: x = 9 + -7x + 6x + 4x2 Combine like terms: -7x + 6x = -1x x = 9 + -1x + 4x2 Solving x = 9 + -1x + 4x2 Solving for variable 'x'. Reorder the terms: -9 + x + x + -4x2 = 9 + -1x + 4x2 + -9 + x + -4x2 Combine like terms: x + x = 2x -9 + 2x + -4x2 = 9 + -1x + 4x2 + -9 + x + -4x2 Reorder the terms: -9 + 2x + -4x2 = 9 + -9 + -1x + x + 4x2 + -4x2 Combine like terms: 9 + -9 = 0 -9 + 2x + -4x2 = 0 + -1x + x + 4x2 + -4x2 -9 + 2x + -4x2 = -1x + x + 4x2 + -4x2 Combine like terms: -1x + x = 0 -9 + 2x + -4x2 = 0 + 4x2 + -4x2 -9 + 2x + -4x2 = 4x2 + -4x2 Combine like terms: 4x2 + -4x2 = 0 -9 + 2x + -4x2 = 0 Begin completing the square. Divide all terms by -4 the coefficient of the squared term: Divide each side by '-4'. 2.25 + -0.5x + x2 = 0 Move the constant term to the right: Add '-2.25' to each side of the equation. 2.25 + -0.5x + -2.25 + x2 = 0 + -2.25 Reorder the terms: 2.25 + -2.25 + -0.5x + x2 = 0 + -2.25 Combine like terms: 2.25 + -2.25 = 0.00 0.00 + -0.5x + x2 = 0 + -2.25 -0.5x + x2 = 0 + -2.25 Combine like terms: 0 + -2.25 = -2.25 -0.5x + x2 = -2.25 The x term is -0.5x. Take half its coefficient (-0.25). Square it (0.0625) and add it to both sides. Add '0.0625' to each side of the equation. -0.5x + 0.0625 + x2 = -2.25 + 0.0625 Reorder the terms: 0.0625 + -0.5x + x2 = -2.25 + 0.0625 Combine like terms: -2.25 + 0.0625 = -2.1875 0.0625 + -0.5x + x2 = -2.1875 Factor a perfect square on the left side: (x + -0.25)(x + -0.25) = -2.1875 Can't calculate square root of the right side. The solution to this equation could not be determined.
| h+7=2h+14-9 | | 20s=89 | | t(x)=2.4x^2+90.8x+1.59 | | 9x-2x=11 | | 12j-3(j-2)=33 | | 10=8+d+d+d+d | | 4x^2y-16x^2y^2-12xy=0 | | 3x+4x=140 | | 78=3d+12-d+4 | | 0=2.4x^2+90.8x+1.59 | | 4x+42-5x=2-8x+5 | | 8(u-5)+3u=4 | | 8(3m+6)-7(4m-9)=-1 | | z+z+z-10=-1 | | 6+3w=4w | | 18(7-2n)=1(7+2n) | | 3+2p=17 | | 3x+4=28x-78 | | 4x+42-5x=2-8x-5 | | 747=2.4x^2+90.8x+1.59 | | X^3+X^2=576 | | 4t=1.6 | | -13t=-117 | | x-10y=-10 | | B-7.5=1 | | 160=112t-16t | | 6-p=5p+30 | | T-2.2=3.1 | | -3c=3 | | 9w=5(w-14) | | 25x^3-5x^2+8x+2=0 | | -21=y+y+y |